Ocorrência de diapausa em Tenuipalponychus tabebuiae Aguilar, Flechtmann & Ochoa (Acari, Tetranychidae) no Estado de São Paulo, Brasil - Feres, Reinaldo J.F. [UNESP]; Bellini, Marcos R. [UNESP] (Sociedade Brasileira de Zoologia, 2002)
This paper reports the occurrence of diapause in Tenuipalponychus tabebuiae Aguilar, Flechtmann & Ochoa, 1991, for the first time in tropical region, and describes the morphological differences between the diapausing and no-diapausing females.
Occurrence of diapause in Tenuipalponychus tabebuiae Aguilar, Flechtmann & Ochoa (Acari, Tetranychidae) in São Paulo State, Brazil
Keywords: Acari; Tetranychidae; diapause; Brazil